Studi Stilistika al-Quran Kisah Nabi Musa AS dalam QS. al-Baqarah dan QS. al-A’raf - Pachrizal, Ade; Wiwaha, Rizzaldy Satria (Al Maghazi : Arabic Language in Higher Education, 2024)
This research is research analyzing the stylistics of the al-Quran. This research aims to analyze various language styles and expressions of the story of the Prophet Musa as. which is explained in QS. Al-Baqarah and QS. Al-A'rāf. This research uses a qualitative approach with a type of library research based on data collected through documentation techniques. Then the data was analyzed using the content analysis method. The results of this research show that there are a variety of language styles and expressions used in the al-Quran, especially in the story of the Prophet Musa as. influence the meaning, message and impression produced. So that repetitions in the al-Quran must be given more attention to examine the diversity of language styles and expressions.   Keywords: al-Quran, story, language, stylistic